Growth and Survival of Acropora Formosa (Scleractinia: Acroporidae) Coral Fragments and Their Impact on Reef Fish Assemblage in Geluk Island, Terengganu - Ibrahim, Mohd Hairulnizam; Ariffin, Indang Ariati; Yusof, Muhammad Hamizan (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
Coral transplantation is a widely used technique for restoring damaged reefs in order to restore coral abundance, recruitment, and species diversity. However, its limited evidence to prove the impacts on coral reef fish. In this study, the fish abundance was determined before and after a coral transplant project at Geluk island, Terengganu. Prior to the study, branching coral from acropora formosa species were propagated and evaluated for 2 years. The experimental design included a mortality percent and the growth rate of coral fragment used. Correspondingly, quantify the differences in reef fish diversity indices before and after the propagation. Overall, the coral fragment survived at rate of 96%, and the growth rates of fragment ranged between 6.4 ± 0.6 cm/year to 9.5 ± 1.1 cm/year. Pomacentridae was determined to be dominant family for coral reef fish, and the fish species increased in term of their species diversity (H1) from 0.000 (2016) to 1.053 (2017) and 2.076 (2018) respectively. High growth and survival rates of acropora formosa coral fragments and the increases pattern of fish diversity found in this study suggested that the coral propagation is successful and feasible in increasing the fish assemblages.